조립식 수영장을 활용한 중학교 생존수영 수업 지속 과정에 관한 사례연구 - 윤현수(Youn Hyun-Su) (교과교육학연구, 2020)
이 연구는 두 중학교의 조립식 수영장을 활용한 생존수영 수업 지속 과정을 살펴봄으로써 대안적 생존수영 교육의 확장 가능성을 살펴보는데 목적이 있다. 연구 사례는 2019년 7월 한 달간 진행했던 ‘S’시의 ‘K’, ‘Y’ 중학교에서 조립식 수영장을 활용한 생존수영 수업 과정이다. 유목적 표집법 중 결정적 사례 표집을 사용하여 ‘K’, ‘Y’ 중학교의 두 체육교사를 정보제공자로 선정하였다. 자료는 개인면담 2차례 씩 총 4회에 걸쳐 반구조화 된 공식면담과 관련 문서자료를 중심으로 수집하였다. 자료 분석은 두 중학교의 생존수영 수업 지속 과정에 관한 자료를 중심으로 사례 내 분석을 실시하였고 귀납적 분석을 통하여 각 사례의 공통된 핵심 주제를 밝혀내는 사례 간 분석을 병행하였다. 두 체육교사는 조립식 수영장 시설과 부대시설을 설치하여 생존수영 수업을 준비하였다. 정규수업과 교과 외 시간을 확보하여 생존수영 프로그램을 운영하였다. 또한, 실제 상황을 가정한 생존수영 중심의 내용과 팀티칭 및 수준별 수업을 도입하였다. 학생들에게 자유롭게 수영복을 착용하도록 하였고, 수질 관리를 위해 노력하였다. 이러한 조립식 수영장을 활용한 생존수영 수업은 ‘따라 하기’ 따져 하기‘라는 두 가지 전략에 의해 지속된 것으로 해석되었다. The purpose of this study is to examine the possibility of expansion of alternative survival swimming education by examining the continuation process of survival swimming classes, using assembly swimming pools at two middle schools. The study case is a survival swimming class using an assembly swimming pool at the ‘K’ and ‘Y’ middle schools in the city of ‘S’ for a month in July 2019. Two physical education teachers of ‘K’ and ‘Y’ middle schools were selected and provided information, using decisive case sampling among the critical case sampling. The data was collected mainly from semistructured official interviews and related document, in total four times of individual interview with two sessions for each. For data analysis, in-case analysis was conducted, focusing on data on the continuation of the survival lessons of the two middle schools, and inductive analysis was applied to reveal common core themes of each case. The two physical education teachers prepared for the survival swimming class by installing assembly swimming pool facilities and additional facilities. Survival swimming programs were run in extracurricular time, outside of the regular curriculum. Also, the contents of team teaching and level of survival and swimming were adopted, assuming the actual situation. Students were allowed to wear swimsuits they want, and efforts were made to manage water quality. It is interpreted that the survival swimming class using this assembly swimming pool has two educational implications of ‘following’ and ‘getting off’. KCI Citation Count: 0